KONSEP KURIKULUM PENDIDIKAN AGAMA ISLAMDI LEMBAGA PENDIDIKAN DI INDONESIA - Muhammad Kholik; Zaianal Efendi Hasibuan; Zuhra Yanti (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
This research examines the concept of the Islamic religious education curriculum in educational institutions in Indonesia. The Islamic religious education curriculum plays an important role in shaping students' moral and spiritual values, and preparing them to contribute positively to society. This research uses a qualitative approach with literature study methods and in-depth interviews with educational experts and practitioners at Islamic educational institutions. The research results show that the concept of the Islamic religious education curriculum in Indonesia is designed not only to provide religious knowledge, but also to shape the character of students so that they are by Islamic values. However, this research also found several challenges in implementing the curriculum, such as a lack of integration between theory and practice, and limited educational resources and facilities. This research identifies several strategies to increase the effectiveness of the Islamic religious education curriculum, including developing learning modules that are more relevant to local contexts, improving the quality of teacher training, and utilizing technology in the learning process. This research concludes that developing a comprehensive and dynamic Islamic religious education curriculum is very important to answer the challenges of the times and support the creation of a generation with noble character and broad knowledge.